Investigations of new five-coordinate dinuclear Co(II) and Cu(II) salamo-based complexes. Issue 17 (26th January 2022) - Zhang, Yang; Li, Li-Li; Huang, Ying; Feng, Tao; Dong, Wen-Kui
Abstract: A new salamo-based ligand and its two new dinuclear complexes [{Co(L)}2 (4, 4′-bipy)] (1 ) and [{Cu(L)}2 ] (2 ), were designed and self-assembled, and characterized by elemental analyses, FT-IR, UV–vis absorption spectroscopy and X-ray crystallography. In 1, two [Co(L)] units are bridged by the auxiliary bidentate ligand 4, 4′-bipy with nitrogen-donor atoms to form a centrosymmetric dimeric structure. Both Co(II) ions are five-coordinate and possess distorted trigonal bipyramidal configurations. Complex 2 is composed of two Cu(II) ions and two completely deprotonated ligand (L) 2– units. Interestingly, the two [Cu(L)] units form a dimer bridged by two oxime O atoms. This structure is rare in reported salamo-based Cu(II) complexes. Both Cu(II) ions are five-coordinate and possess distorted tetragonal pyramidal geometries. Hirshfeld surface analyses showed that the O–H/H–O interactions of 1 and 2 are weaker than that of H2 L. This phenomenon indicates that H2 L forms corresponding complexes with the Co(II) and Cu(II) ions through the deprotonation of phenolic hydroxyl groups. The fluorescence spectra showed that the fluorescence of the ligand is almost completely quenched due to the coordination of the Cu(II) ions with H2 L. DFT calculations show that 1 and 2 have higher chemical stability than that of H2 L. Graphical Abstract: UF0001